THE DISTRIBUTION, IMPORTANCE, BIOLOGY AND CONTROL, OF CHROMOLAENA ODORATA (L.) K.& R.A MAJOR WEED SPECIES OF COCONUT PLANTATION IN SRI LANKA - T.G.L.G. Gunasekara (International Coconut Community Journal, 1995)
Chromolaena odorata (1.) K. & R. is a tropical perennial weed species qf the Asteraceae family that has become a serious problem in coconut plantations in Sri Lanka and in the tropics of Asia and Africa. The history of distribution, habitat and economic importance is summarized The botanical features and seed biology of this species are presented in this review Finally information on the control measures such as mechanical, cultural, chemical and biological methods is discussed.